Invisible exiles? An African-South African woman's reconfiguration of 'exile' in Jeremiah 21:1-10 - Masenya, Madipoane (Old Testament essays, 2007)
The notion of exile is usually linked to a (forced) movement of a person from the country of her / his birth to another country. This also underlies the pericope under discussion in the present text, that is, Jer 21:1-10. The word 'exile' can also be linked with negative experiences such as lack of freedom, assimilation into foreignness, xenophobia and even death. Some of these life-denying experiences typify the experiences of 'exiled' African-South African women. According to Jer 21:8-10, though, there can be life in exile. Jeremiah's exhortation forms part of the Grand Narrative of exile in the Jeremiah tradition. This implies that there are other 'shades' of exile told in 'exile' stories which are not given as much attention as the meta-narrative by the book of Jeremiah. These are as invisible as the exile stories of African-South African women. By looking through the lens of the metaphor of 'women-in-exile-at-home', what insights can Jer 21:8-10 give? Recognising that African-South African women's 'exile' stories are invisible when compared to the Grand Narrative of exile in post-apartheid South African politics, in what way can the words of Jer 21:8-10 be configured using present day South Africa as frame of reference? These are the questions grappled with in this article.